Low-quality quartz ore purification process
By adopting multi-stage flotation and pickling methods in the quartz ore purification process, the problem of difficulty in removing impurities in low-quality quartz ore is solved, and the production of high-purity quartz sand is achieved, reducing costs and environmental impacts.
Patent Information
- Application Number
- CN202411696091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively purify low-quality quartz ores containing a variety of impurities, resulting in scarce high-purity quartz resources.
Using the techniques of crushing, roll crushing and screening closed circuit cycle, rod grinding ore graded closed circuit cycle, desilting, magnetic separation, multi-stage ore dressing and acid leaching, the impurities are removed through multi-stage flotation and acid washing to improve the purity of quartz ore .
It effectively improves the purity of low-quality quartz ore, reduces the amount of hydrofluoric acid, reduces the cost and environmental impact, and realizes the production of high-purity quartz sand.
Smart Images

Figure CN119425949A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mining engineering, and in particular to a purification process for low-quality quartz ore. Background Art
[0002] Quartz sand is an important industrial mineral raw material, widely used in glass, casting, chemical industry, petroleum and other industrial sectors. Quartz sand mineral resources are abundant in the world. Quartz is one of the most common rock-forming minerals in nature. The global quartz resources are very rich and widely distributed. The types of deposits that can be developed mainly include quartz sandstone, quartzite, natural quartz sand, powder quartz, granite quartz, natural crystal, vein quartz, etc. Although the global quartz resources are abundant, the quartz resources that can be processed into high-purity quartz are very scarce. The global high-purity quartz deposits are mainly distributed in the United States, Australia, Norway, Russia, India, Canada, Brazil and Madagascar. At present, the global resources that can be processed into 3N grade and above high-purity quartz are about 70 million tons. The distribution of high-purity quartz resources is relatively concentrated, mainly distributed in Brazil (21.11 million tons), the United States (18.22 million tons), Canada (10 million tons) and other countries. The amount of high-end, high-purity quartz resources that can be processed into 4N5 grade and above quality is about 20 million tons, 90% of which are concentrated in the United States (18.22 million tons).
[0003] High-purity quartz has extremely low content of impurity elements and fluid inclusions, and has excellent physical and chemical properties such as high temperature resistance, corrosion resistance, high strength, high light transmittance, low thermal expansion coefficient, and good insulation. It is an important raw material for manufacturing quartz crucibles, quartz tubes, quartz flanges, quartz bells, quartz ingots, optical devices, optical fibers and other quartz glass products, electronic-grade industrial silicon (mostly made of 3N grade quartz) and electronic-grade silicon powder. Quartzite is mostly distributed in Sichuan, Anhui, Hunan, Jiangsu, Zhejiang and Shandong; quartz sandstone and natural quartz sand are widely distributed in Sichuan, Fujian, Guangdong, Xinjiang, southern Guangxi, northwest Hainan and northern Shandong, these coastal areas; vein quartz is distributed in metamorphic rock areas in Sichuan, Heilongjiang, Hubei, Jiangsu and other places. In 2022, the national quartzite reserves are about 1.364 billion tons, quartz sandstone is 1.362 billion tons, vein quartz is 79.27 million tons, crystal is about 541 tons, and powder quartz is 6.31 million tons. No related deposits of granite pegmatite-type high-purity quartz have been found in the country, and there are currently no special reserve statistics.
[0004] In the "Experimental Study on the Preparation of 4N5 Grade High Purity Quartz Sand from a Quartz Vein in Jiangxi", the SiO2 content of a quartz sample in Jiangxi is 98.47%, of which the impurity Al content is 6073.67ppm, the Fe content is 4796.43ppm, and the K and Na content are both higher than 1000ppm. The experiment adopts the process of crushing and grinding-screening-4-stage magnetic separation-2-stage scrubbing-2-stage water washing-2-stage flotation-2-stage de-doping-roasting-water quenching-acid leaching to purify the quartz sand. After 4 stages of magnetic separation, the SiO2 content of the quartz sand was 99.49%, and the Fe content was reduced to 187.51ppm; after scrubbing, the SiO2 content of the quartz sand was 99.57%, and after flotation, the SiO2 content was 99.972%. 40mL of hydrofluoric acid was used for acid leaching, and the total impurity element content of the final product quartz sand was 54.84ppm, of which the Al content was 16.76ppm, the Na content was 5.83ppm, the K content was 6.46ppm, and the Fe content was 17.50ppm. The SiO2 content was greater than or equal to 99.995%, meeting the requirements of 4N5 grade high-purity quartz sand products. The quartz sample has fewer impurities, does not contain mica, feldspar and other impurities that are difficult to handle, and the experimental process is complex and has poor applicability.
[0005] It is difficult to obtain high-quality silica from quartz ores that contain various impurities such as mica, feldspar, rutile, barite, and iron-containing minerals containing aluminum, iron, barium, and titanium. Therefore, a process for purifying low-quality quartz ores is urgently needed. Summary of the invention
[0006] The purpose of the present invention is to provide a low-quality quartz ore purification process. The present invention removes rutile and barite by gravity separation or flotation, removes mica and feldspar by flotation, and finally removes impurities such as iron and aluminum by pickling. The acid leaching solution is reused to save the amount of acid, and the tailings and concentrates are used for different purposes. It not only effectively improves the purity of low-quality quartz ore and improves the grade of silica, but also reduces the amount of hydrofluoric acid, which not only reduces costs, but also reduces the impact on the environment.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The invention provides a low-quality quartz ore purification process, comprising crushing, roller crushing and screening closed-circuit circulation, rod mill grinding and classification closed-circuit circulation, desludging, magnetic separation, multi-stage mineral separation and acid leaching.
[0009] Further, on the basis of the above technical solution, the crushing includes: feeding the ore block into a jaw crusher to obtain a first crushing product;
[0010] Preferably, the particle size of the first crushed product is 0-5 mm;
[0011] Preferably, the ore block is quartz ore with a particle size of 0-150 mm;
[0012] Preferably, the quartz ore comprises, by mass percentage: 90.0-96.0% SiO2 and impurity elements;
[0013] Preferably, the impurity elements include: 0-3.0% Al2O3, 0-5.0% TFe, 0.3-3.0% K2O, 0.05-2.0% BaO, 0.03-2.0% TiO2;
[0014] Preferably, the impurity minerals in the quartz ore include muscovite, limonite, hematite, barite, biotite, potassium feldspar, albite, rutile and apatite.
[0015] Further, on the basis of the above technical solution, the double roller crushing and screening closed-loop cycle includes: feeding the first crushed product into a first fine screen to obtain a first over-screen product and a first under-screen product;
[0016] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation;
[0017] All the undersize products obtained through the first fine screen are fed to the next process;
[0018] Preferably, the mesh diameter of the first fine sieve is 1.8-2.2 mm.
[0019] Further, on the basis of the above technical solution, the rod mill grinding classification closed-loop cycle includes: feeding all undersize products obtained through the first fine screen into the second fine screen to obtain a second oversize product and a second undersize product;
[0020] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0021] All the undersize products obtained by the second fine screen are fed to the next process;
[0022] Preferably, the mesh diameter of the second fine sieve is 0.6-0.8 mm;
[0023] Preferably, the grinding is stopped when the particle size of the grinding product is in the range of 0.1 mm to 0.8 mm;
[0024] Preferably, the mass fraction of the feed concentration in the rod mill is 62% to 70%.
[0025] Further, on the basis of the above technical solution, the desliming comprises: feeding all the undersize products obtained through the second fine screen into a stirring barrel to obtain deslimed tailings and deslimed concentrate;
[0026] The deslimed concentrate is fed to the next operation;
[0027] Preferably, the stirring speed of the stirring barrel is 600-1000 r / min, and the mass fraction of the slurry concentration is 20-40%;
[0028] Preferably, the SiO2 grade in the deslimed concentrate is greater than 96.5%.
[0029] Further, on the basis of the above technical solution, the magnetic separation comprises: feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0030] The magnetic concentrate is fed to the next operation;
[0031] The magnetic field strength of the magnetic separator is 1.0T to 1.6T, the magnetic bar medium is 1.0 to 2.0mm, the magnetic separation concentration is 25% to 35%, and the pulsation frequency is 25 to 100 times / min;
[0032] Preferably, the SiO2 grade in the magnetic separation concentrate is greater than 98%.
[0033] Further, on the basis of the above technical solution, the multi-stage mineral separation includes gravity separation and second flotation,
[0034] Or, first flotation and second flotation.
[0035] Further, on the basis of the above technical solution, the first flotation comprises: feeding the magnetic concentrate into the first flotation to obtain the first flotation tailings and the first flotation concentrate;
[0036] The first flotation concentrate is fed to the next operation;
[0037] Preferably, the mass fraction of the feed concentration in the first flotation is 20%-40%;
[0038] Preferably, the collector in the first flotation is a combined collector including SLH and ZP-01;
[0039] Preferably, the mass ratio of SLH to ZP-01 is 1:(1-3), and the addition amount of the combined collector is 500-700 g / t;
[0040] Preferably, the amount of water glass in the first flotation is 450-600 g / t;
[0041] Preferably, the SiO2 grade in the first flotation concentrate is greater than 98.90%;
[0042] Gravity separation includes: feeding the magnetic separation concentrate into gravity separation to obtain gravity separation tailings and gravity separation concentrate; feeding the gravity separation concentrate into the next operation;
[0043] Preferably, the mass fraction of the feed concentration in the reselection is 10%-25%;
[0044] Preferably, the amount of flushing water in the reselection is 1.0 to 2.0 t / h;
[0045] Preferably, the gravity separation equipment is a spiral chute or a shaking table;
[0046] Preferably, the SiO2 grade in the gravity separation concentrate is greater than 98.80%.
[0047] Further, on the basis of the above technical solution, the second flotation comprises: feeding the first flotation concentrate or the gravity separation concentrate into the second flotation to obtain the second flotation tailings and the second flotation concentrate;
[0048] The second flotation concentrate is fed to the next operation;
[0049] Preferably, the mass fraction of the feed concentration in the second flotation is 30%-40%.
[0050] Preferably, the collector in the second flotation is LGB-01, and its addition amount is 50-150 g / t;
[0051] Preferably, the amount of sulfuric acid used in the second flotation is 3200-50000 g / t;
[0052] Preferably, the amount of HF used in the second flotation is 100-300 g / t;
[0053] Preferably, the SiO2 grade in the second flotation concentrate is greater than 99.15%.
[0054] Further, on the basis of the above technical solution, the acid leaching comprises: subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leached concentrate;
[0055] The leached concentrate is the final product;
[0056] Preferably, the mass fraction of the feed concentration in the acid leaching is 25%-50%;
[0057] Preferably, the acid leaching solution comprises water, hydrochloric acid and hydrofluoric acid in a volume ratio of 5:(2-4):(1.5-2.5);
[0058] Preferably, the acid leaching temperature is 70°C to 95°C;
[0059] Preferably, the acid leaching time is 5 to 7 hours;
[0060] Preferably, the SiO2 grade in the leached concentrate is greater than 99.90%.
[0061] The present invention provides a low-quality quartz ore purification process, which has the following beneficial effects:
[0062] (1) The present invention adopts a process of more crushing and less grinding, and the process cost is relatively low;
[0063] (2) The present invention can obtain qualified particle size products (particle size of 0.6-0.8 mm) in steps by setting up a rod mill grinding and grading closed-loop circulation. The present invention adopts a rod mill for grinding. The rod mill is in line contact during the grinding process and can crush large particles to a limited extent. Therefore, the obtained product particle size is coarser. Some qualified particle size products can be obtained through the second fine screen. Unqualified minerals are continuously fed into the rod mill and screened again to obtain some qualified particle size products, thus forming a cycle. Compared with the ball milling process used in the prior art, the obtained product particle size is coarser and the fine particles will not be over-crushed.
[0064] (3) The present invention performs preliminary screening through the first screening, and can first obtain some qualified particle products, without the need for grinding treatment of the qualified particle products, thus avoiding the phenomenon of over-crushing of the products;
[0065] (4) The present invention uses the first flotation or gravity separation to remove barite and rutile, and the second flotation to remove feldspar and mica, which not only improves the stability of silica processing, but also improves the quality of the product, providing reliable technical support for the application expansion of silica;
[0066] (5) The present invention realizes comprehensive utilization of resources and has fewer tails;
[0067] (6) The present invention uses mixed acid in acid leaching to obtain high-grade silica.
[0068] (7) The main impurities of silica used in the present invention are mica, feldspar, rutile, barite and iron-containing minerals containing aluminum, iron, barium and titanium. It is difficult to obtain high-quality silica. The present invention removes rutile and barite by gravity separation or first flotation, and then removes mica and feldspar by second flotation. Finally, impurities such as iron and aluminum are further removed by pickling. The amount of acid is saved by recycling the acid leaching solution, so that the tailings and concentrates can be used for different purposes. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0070] Figure 1 A schematic diagram of a low-quality quartz ore purification process provided in Example 1 of the present invention;
[0071] Figure 2 A schematic diagram of a low-quality quartz ore purification process provided in Examples 2-4 of the present invention. DETAILED DESCRIPTION
[0072] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0073] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0074] According to a first aspect of the present invention, a low-quality quartz ore purification process is provided, comprising crushing, roller crushing and screening closed-circuit circulation, rod mill grinding and classification closed-circuit circulation, desludging, magnetic separation, multi-stage mineral separation and acid leaching.
[0075] As an optional embodiment of the present invention, the crushing includes:
[0076] Feeding the ore block into the jaw crusher to obtain the first crushing product;
[0077] The particle size of the first crushed product is 0-5 mm (such as 1 mm, 2 mm, 3 mm, 4 mm, etc.).
[0078] As an optional embodiment of the present invention, the ore block is quartz ore with a particle size of 0-150 mm (such as 50 mm, 70 mm, 90 mm, 110 mm, 130 mm, etc.), and the impurity elements in the quartz ore include Al, Fe, K, Ba and Ti;
[0079] In terms of mass percentage, the quartz ore includes: 90.0-96.0% (e.g., 91%, 92%, 93%, 94%, 95%, etc.) of SiO2 and impurity elements;
[0080] Preferably, the impurity elements include: 0-3.0% (e.g., 1%, 2%, etc.) of Al2O3, 0-5.0% (e.g., 1%, 2%, 3%, 4%, etc.) of TFe, 0.3-3.0% (e.g., 1%, 2%, etc.) of K2O, 0.05-2.0% (e.g., 0.5%, 1%, 1.5%, etc.) of BaO, 0.03-2.0% (e.g., 0.5%, 1%, 1.5%, etc.) of TiO2;
[0081] The impurity minerals in the quartz ore include muscovite, limonite, hematite, barite, biotite, potassium feldspar, albite, rutile and apatite.
[0082] Specifically, since there are many impurities in the above-mentioned quartz ore, the present invention adopts magnetic separation to remove iron in the ore, and first removes impurity elements such as barium and titanium in the ore through multi-stage flotation, and then removes feldspar and mica in the ore.
[0083] As an optional embodiment of the present invention, the roller crushing and screening closed-loop cycle includes:
[0084] Feeding the first crushed product into a first fine screen to obtain a first oversize product and a first undersize product;
[0085] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen again to form a closed loop;
[0086] All the undersize products obtained by the first fine screen are fed to the next process.
[0087] Specifically, the present invention adopts a screening-crushing-roller grinding closed-loop circulation process, and can obtain qualified particle size products (particle size is 1.8-2.2mm) in steps; the product particle size of the roller crushing adopted in the present invention is coarser, and some qualified particle size products can be obtained through the first fine screen, and unqualified minerals are continuously fed into the roller crusher, and then screened to obtain some qualified particle size products, thus forming a cycle; compared with the direct grinding process after crushing in the prior art, the obtained product particle size is coarser, and the fine particles will not be over-crushed, which affects the yield.
[0088] As an optional embodiment of the present invention, the mesh diameter of the first fine screen is 1.8-2.2 mm (such as 1.9 mm, 2 mm, 2.1 mm, etc.).
[0089] As an optional embodiment of the present invention, the rod mill grinding and classification closed-loop circulation comprises:
[0090] Feeding all undersize products obtained through the first fine sieve into a second fine sieve to obtain a second oversize product and a second undersize product;
[0091] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0092] All the undersize products obtained by the second fine screen are fed to the next process;
[0093] The mesh diameter of the second fine sieve is 0.6-0.8 mm (e.g., 0.65 mm, 0.7 mm, 0.75 mm, etc.);
[0094] When the particle size of the grinding product is within the range of 0.1mm to 0.8mm, stop grinding;
[0095] The mass fraction of the feed concentration in rod mill grinding is 62% to 70% (such as 63%, 65%, 67%, 69%, etc.).
[0096] Specifically, the present invention can also achieve step-by-step acquisition of qualified particle size products (particle size of 0.6-0.8mm) by setting up a rod mill grinding and grading closed-loop circulation. The present invention adopts a rod mill for grinding. The rod mill is in line contact during the grinding process and large particles are crushed to a limited extent, so the obtained product particle size is coarser. Some qualified particle size products can be obtained through the second fine screen. Unqualified minerals are continuously fed into the rod mill and screened again to obtain some qualified particle size products, thus forming a cycle. Compared with the ball milling process used in the prior art, the obtained product particle size is coarser, and the fine particles will not be over-crushed, which affects the yield.
[0097] Furthermore, the present invention can maximize the yield of the minerals with a particle size of 40-140 meshes, which can reach 70-85%, by combining the closed-circuit cycle of roller crushing and screening and the closed-circuit cycle of rod mill grinding and classification. Quartz ore with this particle size has a wide range of uses because of its moderate particle size, which not only maintains good physical and chemical properties, but also has high processing performance.
[0098] As an optional embodiment of the present invention, the desludging comprises:
[0099] Feeding all the undersize products obtained through the second fine screen into a mixing barrel to obtain deslimed tailings and deslimed concentrates;
[0100] The deslimed concentrate is fed to the next operation;
[0101] The stirring speed of the stirring barrel is 600-1000 r / min (such as 700 r / min, 800 r / min, 900 r / min, etc.), and the mass fraction of the slurry concentration is 20-40% (such as 25%, 30%, 35%, etc.);
[0102] Specifically, the present invention limits the stirring speed of the stirring barrel to 600-1000r / min. If the speed is too low, the desludging effect will not be ideal, not only the processing time is long, but also the solid particles in the mud are difficult to fully separate, resulting in poor overall desludging effect; and if the speed is too high, the amount of fine mud will increase accordingly, and the silicon component in the fine mud will be more easily lost, resulting in a large loss of silicon. Therefore, controlling the stirring speed within the range of 600-1000r / min can reduce the loss of silicon while ensuring the desludging effect, thereby improving the efficiency and economic benefits of the overall process.
[0103] The SiO2 grade in the deslimed concentrate is greater than 96.5%.
[0104] Specifically, the desludging process can effectively remove the silt, clay and fine-grained minerals attached to the surface of the mineral. The mineral slurry is scrubbed by stirring, and the mechanical force is used to destroy the adhesion of silt and clay to the silica surface, so that these impurities are separated from the mineral surface, thereby improving the silica grade.
[0105] As an optional embodiment of the present invention, the magnetic separation comprises:
[0106] Feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0107] The magnetic concentrate is fed to the next operation;
[0108] The magnetic field strength of the magnetic separator is 1.0T to 1.6T (such as 1.1T, 1.2T, 1.3T, 1.4T, 1.5T, etc.), the magnetic bar medium is 1.0 to 2.0mm (such as 1.2mm, 1.4mm, 1.6mm, 1.8mm, etc.), the magnetic separation concentration is 25% to 35% (such as 27%, 29%, 31%, 33%, etc.), and the pulsation frequency is 25 to 100 times / min (such as 30 times / min, 50 times / min, 70 times / min, 90 times / min, etc.);
[0109] The SiO2 grade in the magnetic separation concentrate is greater than 98%.
[0110] Specifically, if the magnetic field intensity is low, it will cause some weak magnetic minerals, magnetic inclusions or large-grained silica that are not dissociated to enter non-magnetic silica, resulting in a reduction in silica grade. If the magnetic field intensity is high, some silica particles that were originally non-magnetic will be mistakenly classified as magnetic materials due to magnetic agglomeration, causing this part of silica to be mistakenly separated, which will also reduce the grade of silica. Excessive magnetic field intensity may also increase energy consumption during magnetic separation and increase production costs. Therefore, the present invention aims to optimize the magnetic separation effect by controlling the magnetic field intensity between 1.0T and 1.6T, ensuring that magnetic minerals are effectively separated, while avoiding the reduction in silica grade or the increase in production costs caused by improper magnetic field intensity. Such a setting helps to improve the efficiency of magnetic separation technology, ensure the quality of silica products, and improve silica grade.
[0111] As an optional embodiment of the present invention, the multi-stage mineral separation includes gravity separation and second flotation.
[0112] Or, first flotation and second flotation.
[0113] As an optional embodiment of the present invention, the first flotation comprises: feeding the magnetic concentrate into the first flotation to obtain the first flotation tailings and the first flotation concentrate;
[0114] The first flotation concentrate is fed to the next operation;
[0115] The mass fraction of the feed concentration in the first flotation is 20%-40% (such as 25%, 30%, 35%, etc.); when the feed concentration is very low, the recovery rate is usually low. As the feed concentration gradually increases, the recovery rate will also gradually increase, and reach a maximum value at a concentration of 20%-40%. However, if the pulp concentration is too high and exceeds the optimal concentration range, the recovery rate will decrease. This is because too high or too low feed concentration will deteriorate the aeration conditions of the flotation machine, thereby affecting the recovery rate.
[0116] The collectors in the first flotation are combined collectors, including SLH (the main components include alkyl hydroxamic acid, salicylic hydroxamic acid and No. 2 oil in a mass ratio of 1:1:(0.2-0.5)) and ZP-01 (the main components include alkyl hydroxamic acid and benzohydroxamic acid in a mass ratio of 1:1), which are selectively adsorbed on the surface of the first flotation concentrate mainly through their specific chemical properties. This adsorption changes the physical properties of the surface of the first flotation concentrate, such as wettability and hydrophobicity. Specifically, the collectors reduce the hydrophilicity of the mineral surface and increase the hydrophobicity. When the surface of the first flotation concentrate becomes sufficiently hydrophobic, they can effectively attach to the bubbles generated during the flotation process. These minerals attached to the bubbles are then brought to the surface of the flotation tank to form a foam layer, which can be separated from the pulp by scraping or overflowing. In addition, conventional quartz ore usually contains more sulfur impurities, so it is necessary to use xanthate, black powder and other collectors to remove sulfur impurities in the ore, but the present invention does not contain sulfur impurities, so SLH and ZP-01 are used as combined collectors, which can react with easily floating minerals such as barium titanium minerals to enhance their adhesion to bubbles, thereby effectively separating these minerals during the flotation process. In this way, the present invention can improve the purity of quartz minerals and the grade of silica to meet standard application requirements.
[0117] The mass ratio of SLH to ZP-01 is 1:(1-3), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3, etc. The addition amount of the combined collector is 500-700 g / t (such as 550 g / t, 600 g / t, 650 g / t, etc.);
[0118] The amount of water glass used in the first flotation is 450-600 g / t (such as 470 g / t, 500 g / t, 520 g / t, 550 g / t, 570 g / t, etc.). Water glass can form complexes with metal ions on the surface of mineral particles, increase the wettability and hydrophilicity of mineral particles, thereby enhancing their buoyancy in water and accelerating flotation separation;
[0119] The SiO2 grade in the first flotation concentrate is greater than 98.90%.
[0120] As an optional implementation manner of the present invention, the reselection includes:
[0121] Feeding the magnetic separation concentrate into gravity separation to obtain gravity separation tailings and gravity separation concentrate;
[0122] The re-selected concentrate is fed to the next operation;
[0123] The mass fraction of the feed concentration in the reselection is 10%-25% (such as 12%, 15%, 17%, 21%, 23%, etc.), and the basis for selecting the feed concentration in the reselection is as above;
[0124] The amount of flushing water in gravity separation is 1.0-2.0 t / h (1.2 t / h, 1.4 t / h, 1.6 t / h, 1.8 t / h, etc.). Flushing water can improve the fluidity of minerals, making them easier to move and separate during separation, thus improving separation efficiency.
[0125] The gravity separation equipment is a spiral chute or a shaking table;
[0126] The SiO2 grade in the gravity separation concentrate is greater than 98.80%.
[0127] Specifically, due to the large difference in density between barium-titanium minerals (baryte, rutile, etc.) and silica, the barium-titanium minerals can be separated from silica through the first flotation or gravity separation, and the reduction of impurity content will increase the grade of silica.
[0128] As an optional embodiment of the present invention, the second flotation comprises: feeding the first flotation concentrate or gravity separation concentrate into the second flotation to obtain the second flotation tailings and the second flotation concentrate;
[0129] The second flotation concentrate is fed to the next operation;
[0130] And / or, the mass fraction of the feed concentration in the second flotation is 30%-40% (such as 32%, 34%, 36%, 38%, etc.), and the feed concentration in the second flotation is selected based on the above;
[0131] and / or, the collector in the second flotation is LGB-01 (mainly composed of alkyl hydroxamic acid and salicylic hydroxamic acid in a mass ratio of 1:1), and the addition amount thereof is 50 to 150 g / t (e.g., 70 g / t, 90 g / t, 110 g / t, 130 g / t, etc.);
[0132] And / or, the amount of sulfuric acid used in the second flotation is 3200-50000 g / t (such as 4000 g / t, 6000 g / t, 8000 g / t, 10000 g / t, 20000 g / t, 30000 g / t, 40000 g / t, etc.), and sulfuric acid is mainly used as an adjuster in flotation to adjust the pH value of the slurry. In flotation separation, sulfuric acid, as a pH adjuster, can help adjust the pH value of the slurry to an appropriate range, usually adjusting the pH value to 2-3. Such a pH environment helps to break the dissociation equilibrium on the mineral surface, thereby affecting the flotation of mineral particles and improving the flotation effect;
[0133] And / or, the amount of HF used in the second flotation is 100-300 g / t (such as 120 g / t, 140 g / t, 160 g / t, 180 g / t, 200 g / t, 220 g / t, 240 g / t, 260 g / t, 280 g / t, etc.). In the flotation separation, hydrofluoric acid can inhibit the floating property of quartz. This is because hydrofluoric acid has a corrosive effect on the Si-O bonds on the surface of quartz, thereby changing the properties of the quartz surface and making it difficult to float out. At the same time, hydrofluoric acid can also activate the surface of feldspar, separate mica and feldspar from silica, and make mica and feldspar easier to float out. This is achieved by forming specific complex ions and combining with ions on the surface of feldspar;
[0134] The SiO2 grade in the second flotation concentrate is greater than 99.15%.
[0135] As an optional embodiment of the present invention, the acid leaching comprises: subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate;
[0136] The leached concentrate is the final product;
[0137] And / or, the mass fraction of the feed concentration in the acid leaching is 25%-50% (such as 30%, 32%, 34%, 36%, 38%, 42%, 44%, 46%, 48%, etc.);
[0138] And / or, the acid leaching solution comprises water, hydrochloric acid and hydrofluoric acid in a volume ratio of 5:(2-4):(1.5-2.5), such as 5:2:1.7, 5:2:2, 5:3:2, 5:3:2.1, 5:4:2.3, etc.;
[0139] and / or, the acid leaching temperature is 70° C. to 95° C. (e.g., 75° C., 80° C., 85° C., 90° C., etc.);
[0140] And / or, the acid leaching time is 5 to 7 hours (5.5 hours, 6 hours, 6.5 hours, etc.);
[0141] The SiO2 grade in the leached concentrate is greater than 99.90%.
[0142] Specifically, the present invention uses mixed acid to remove metal impurities such as iron and aluminum in the ore during the acid leaching process. The synergistic effect of various acid components in the mixed acid can more thoroughly dissolve and remove metal impurities in the ore. The mixed acid uses hydrochloric acid and hydrofluoric acid, which can remove most of the aluminum through flotation, thereby improving the purity and quality of silica, and reducing the damage to the silica itself, thereby improving the yield of silica; in traditional treatment methods, hydrofluoric acid is one of the commonly used strong acids, but its usage is large and has a certain negative impact on the environment. The present invention significantly reduces the amount of hydrofluoric acid used by using mixed acid, which not only reduces costs but also reduces the impact on the environment.
[0143] As an optional embodiment of the present invention, the leachate is returned to the acid leaching step and can be reused 4-10 times, and finally neutralized and filtered using calcium oxide.
[0144] Specifically, the present invention adopts a circulating leaching process to reduce the amount of acid used. A high-grade quartz ore is obtained through the first flotation (gravity separation) - second flotation - acid leaching process, which is conducive to obtaining high-quality quartz from the ore and expanding the use of the ore.
[0145] As an optional embodiment of the present invention, desludging tailings, magnetic separation tailings, gravity separation tailings or first flotation tailings and second flotation tailings are mixed and used as a raw material for regulating and correcting silicate cement clinker;
[0146] Among them, the SiO2 grade of the desludging tailings is 72-77% (for example, 73%, 74%, 75%, 76%, etc.), the SiO2 grade of the magnetic separation tailings is 74-77% (for example, 75%, 76%, etc.), the SiO2 grade of the gravity separation tailings or the first flotation tailings is 90-94% (for example, 91%, 92%, 93%, etc.), and the SiO2 grade of the second flotation tailings is 99.0-99.4% (for example, 99.1%, 99.2%, 99.3%, etc.).
[0147] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0148] Example 1
[0149] In the quartz ore selected in this embodiment, the SiO2 content is 95.48%, and the impurity elements mainly include: Al2O3 content 2.11%, TFe content 0.44%, K2O content 0.53%, BaO content 0.14%, TiO2 content 0.068%, and the total impurity element content is 4.52%, which is a quartzite ore of lower grade.
[0150] like Figure 1 As shown, a low-quality quartz ore purification process provided in this embodiment is specifically as follows:
[0151] (1) Crushing
[0152] Feeding the quartz ore into a jaw crusher to obtain a first crushed product, wherein the particle size of the first crushed product is 0-5 mm;
[0153] (2) Closed-circuit cycle of roller crushing and screening
[0154] Feeding the first crushed product into a first fine sieve (the sieve hole diameter is 2.0 mm) to obtain a first over-sieve product and a first under-sieve product;
[0155] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation;
[0156] All the undersize products (particle size -2 mm) obtained through the first fine screen are fed to the next process;
[0157] (3) Rod mill grinding and classification closed circuit
[0158] Feed all the undersize products obtained through the first fine sieve into a second fine sieve (the sieve hole diameter is 0.8 mm) to obtain a second oversize product and a second undersize product;
[0159] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0160] The particle size of the grinding product is 0.1 mm to 0.8 mm; the mass fraction of the feed concentration is 70%, and the rod mill grinding is 0.5 min;
[0161] All the undersize products (particle size -0.8 mm) obtained through the second fine screen are fed to the next process;
[0162] (4) Desludging
[0163] Feeding all the undersize products obtained through the second fine screen into a mixing barrel to obtain deslimed tailings and deslimed concentrates;
[0164] The deslimed concentrate is fed to the next operation;
[0165] The stirring speed of the stirring barrel is 800r / min, and the slurry concentration is 30%;
[0166] The SiO2 content in the deslimed concentrate is 96.56%, and the Al2O3 content is 1.45%.
[0167] (5) Magnetic separation
[0168] Feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0169] The magnetic concentrate is fed to the next operation;
[0170] The magnetic field strength of the magnetic separator is 1.3 T, the magnetic rod medium is 1.5 mm, the magnetic separation concentration is 25%, and the pulsation frequency is 50 times / min; the SiO2 grade in the magnetic separation concentrate is 98.51%.
[0171] (6) First flotation
[0172] feeding the magnetic separation concentrate into the first flotation to obtain the first flotation tailings and the first flotation concentrate;
[0173] The first flotation concentrate is fed to the next operation;
[0174] Among them, the mass fraction of the feed concentration is 35%, SLH and ZP-01 are used as combined collectors, the mass ratio of SLH and ZP-01 is 1:2, the addition amount of the combined collector is 600g / t, the amount of water glass is 500g / t, and the SiO2 grade in the first flotation concentrate is 98.90%.
[0175] (7) Second flotation
[0176] feeding the first flotation concentrate to a second flotation to obtain a second flotation tailing and a second flotation concentrate;
[0177] The second flotation concentrate is fed to the next operation;
[0178] Among them, the mass fraction of the feed concentration is 35%; the addition amount of LGB-01 collector is 100g / t; the dosage of sulfuric acid is 4500g / t, the dosage of HF in the second flotation is 200g / t, and the SiO2 grade in the second flotation concentrate is 99.27%.
[0179] (8) Acid leaching
[0180] subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate;
[0181] The leached concentrate is the final product;
[0182] Among them, the solid-liquid mass ratio of the second flotation concentrate and the leaching solution is 1:3; the mass fraction of the feed concentration is 30%; the volume ratio of water, hydrochloric acid and hydrofluoric acid in the acid leaching solution is 5:3:2; the acid leaching temperature is 90°C; the acid leaching time is 6h; the SiO2 grade in the leaching concentrate is 99.9258%, and the total content of impurity elements is 742ppm.
[0183] Example 2
[0184] In the quartz ore selected in this embodiment, the SiO2 content is 95.48%, and the impurity elements mainly include: Al2O3 content 2.11%, TFe content 0.44%, K2O content 0.53%, BaO content 0.14%, TiO2 content 0.068%, and the total impurity element content is 4.52%, which is a quartzite ore of lower grade.
[0185] like Figure 2 As shown, a low-quality quartz ore purification process provided in this embodiment is specifically as follows:
[0186] (1) Crushing
[0187] Feeding the quartz ore into a jaw crusher to obtain a first crushed product, wherein the particle size of the first crushed product is 0-5 mm;
[0188] (2) Closed-circuit cycle of roller crushing and screening
[0189] Feeding the first crushed product into a first fine sieve (the sieve hole diameter is 2 mm) to obtain a first over-sieve product and a first under-sieve product;
[0190] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation;
[0191] All the undersize products (particle size -2 mm) obtained through the first fine screen are fed to the next process;
[0192] (3) Rod mill grinding and classification closed circuit
[0193] Feed all the undersize products obtained through the first fine sieve into a second fine sieve (the sieve hole diameter is 0.8 mm) to obtain a second oversize product and a second undersize product;
[0194] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0195] The particle size of the grinding product is 0.1 mm to 0.8 mm; the mass fraction of the feed concentration is 70%, and the rod mill grinding is 0.5 min;
[0196] All the undersize products (particle size -0.8 mm) obtained through the second fine screen are fed to the next process;
[0197] (4) Desludging
[0198] Feeding all the undersize products obtained through the second fine screen into a mixing barrel to obtain deslimed tailings and deslimed concentrates;
[0199] The deslimed concentrate is fed to the next operation;
[0200] The stirring speed of the stirring barrel is 600r / min, and the slurry concentration is 30%;
[0201] The SiO2 content in the deslimed concentrate is 96.51%, and the Al2O3 content is 1.48%.
[0202] (5) Magnetic separation
[0203] Feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0204] The magnetic concentrate is fed to the next operation;
[0205] The magnetic field strength of the magnetic separator is 1.4 T, the magnetic rod medium is 1.5 mm, the magnetic separation concentration is 25%, and the pulsation frequency is 50 times / min; the SiO2 grade in the magnetic separation concentrate is 98.64%.
[0206] (6) Re-election
[0207] Feeding the magnetically separated concentrate into a spiral chute to obtain gravity separation tailings and gravity separation concentrate;
[0208] The re-selected concentrate is fed to the next operation;
[0209] The mass fraction of the feed concentration is 20%, the flushing water volume is 1.5 t / h, and the SiO2 grade in the gravity separation concentrate is 98.83%.
[0210] (7) Second flotation
[0211] Feeding the re-selected concentrate to the second flotation to obtain the second flotation tailings and the second flotation concentrate;
[0212] The second flotation concentrate is fed to the next operation;
[0213] Among them, the mass fraction of the feed concentration is 35%; the addition amount of LGB-01 collector is 120g / t; the amount of sulfuric acid is 4500g / t, the amount of HF in the second flotation is 230g / t, and the SiO2 grade in the second flotation concentrate is 99.23%.
[0214] (8) Acid leaching
[0215] subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate;
[0216] The leached concentrate is the final product;
[0217] Among them, the solid-liquid mass ratio of the second flotation concentrate and the leaching solution is 1:3; the mass fraction of the feed concentration is 30%; the volume ratio of water, hydrochloric acid and hydrofluoric acid in the acid leaching solution is 5:3:2; the acid leaching temperature is 90°C; the acid leaching time is 6h; the SiO2 grade in the leaching concentrate is 99.9329%, and the total content of impurity elements is 671ppm.
[0218] Example 3
[0219] In the quartz ore selected in this embodiment, the SiO2 content is 95.48%, and the impurity elements mainly include: Al2O3 content 2.11%, TFe content 0.44%, K2O content 0.53%, BaO content 0.14%, TiO2 content 0.068%, and the total impurity element content is 4.52%, which is a quartzite ore of lower grade.
[0220] like Figure 2 As shown, a low-quality quartz ore purification process provided in this embodiment is specifically as follows:
[0221] (1) Crushing
[0222] Feeding the quartz ore into a jaw crusher to obtain a first crushed product, wherein the particle size of the first crushed product is 0-5 mm;
[0223] (2) Closed-circuit cycle of roller crushing and screening
[0224] Feeding the first crushed product into a first fine sieve (the sieve hole diameter is 2 mm) to obtain a first over-sieve product and a first under-sieve product;
[0225] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation;
[0226] All the undersize products (particle size -2 mm) obtained through the first fine screen are fed to the next process;
[0227] (3) Rod mill grinding and classification closed circuit
[0228] Feed all the undersize products obtained through the first fine sieve into a second fine sieve (the sieve hole diameter is 0.8 mm) to obtain a second oversize product and a second undersize product;
[0229] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0230] The particle size of the grinding product is 0.1 mm to 0.8 mm; the mass fraction of the feed concentration is 70%, and the rod mill grinding is 0.5 min;
[0231] All the undersize products (particle size -0.8 mm) obtained through the second fine screen are fed to the next process;
[0232] (4) Desludging
[0233] Feeding all the undersize products obtained through the second fine screen into a mixing barrel to obtain deslimed tailings and deslimed concentrates;
[0234] The deslimed concentrate is fed to the next operation;
[0235] The stirring speed of the stirring barrel is 800r / min, and the slurry concentration is 30%;
[0236] The SiO2 content in the deslimed concentrate is 96.53%, and the Al2O3 content is 1.45%.
[0237] (5) Magnetic separation
[0238] Feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0239] The magnetic concentrate is fed to the next operation;
[0240] The magnetic field strength of the magnetic separator is 1.3 T, the magnetic rod medium is 1.5 mm, the magnetic separation concentration is 25%, and the pulsation frequency is 50 times / min; the SiO2 grade in the magnetic separation concentrate is 98.50%.
[0241] (6) Re-election
[0242] Feeding the magnetically separated concentrate into a spiral chute to obtain gravity separation tailings and gravity separation concentrate;
[0243] The re-selected concentrate is fed to the next operation;
[0244] The mass fraction of the feed concentration is 20%, the flushing water volume is 1.5 t / h, and the SiO2 grade in the gravity separation concentrate is 98.85%.
[0245] (7) Second flotation
[0246] Feeding the re-selected concentrate to the second flotation to obtain the second flotation tailings and the second flotation concentrate;
[0247] The second flotation concentrate is fed to the next operation;
[0248] Among them, the mass fraction of the feed concentration is 35%; the addition amount of LGB-01 collector is 100g / t; the dosage of sulfuric acid is 4500g / t, the dosage of HF in the second flotation is 200g / t, and the SiO2 grade in the second flotation concentrate is 99.23%.
[0249] (8) Acid leaching
[0250] subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate;
[0251] The leached concentrate is the final product;
[0252] Among them, the solid-liquid mass ratio of the second flotation concentrate and the leaching solution is 1:3; the mass fraction of the feed concentration is 30%; the volume ratio of water, hydrochloric acid and hydrofluoric acid in the acid leaching solution is 5:3:2; the acid leaching temperature is 90°C; the acid leaching time is 6h; the SiO2 grade in the leaching concentrate is 99.9243%, and the total content of impurity elements is 757ppm.
[0253] Example 4
[0254] In the quartz ore selected in this embodiment, the SiO2 content is 95.48%, and the impurity elements mainly include: Al2O3 content 2.11%, TFe content 0.44%, K2O content 0.53%, BaO content 0.14%, TiO2 content 0.068%, and the total impurity element content is 4.52%, which is a quartzite ore of lower grade.
[0255] like Figure 2 As shown, a low-quality quartz ore purification process provided in this embodiment is specifically as follows:
[0256] (1) Crushing
[0257] Feeding the quartz ore into a jaw crusher to obtain a first crushed product, wherein the particle size of the first crushed product is 0-5 mm;
[0258] (2) Closed-circuit cycle of roller crushing and screening
[0259] Feeding the first crushed product into a first fine sieve (the sieve hole diameter is 2 mm) to obtain a first over-sieve product and a first under-sieve product;
[0260] The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation;
[0261] All the undersize products (particle size -2 mm) obtained through the first fine screen are fed to the next process;
[0262] (3) Rod mill grinding and classification closed circuit
[0263] Feed all the undersize products obtained through the first fine sieve into a second fine sieve (the sieve hole diameter is 0.8 mm) to obtain a second oversize product and a second undersize product;
[0264] The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0265] The particle size of the grinding product is 0.1 mm to 0.8 mm; the mass fraction of the feed concentration is 70%, and the rod mill grinding is 0.5 min;
[0266] All the undersize products (particle size -0.8 mm) obtained through the second fine screen are fed to the next process;
[0267] (4) Desludging
[0268] Feeding all the undersize products obtained through the second fine screen into a mixing barrel to obtain deslimed tailings and deslimed concentrates;
[0269] The deslimed concentrate is fed to the next operation;
[0270] The stirring speed of the stirring barrel is 600r / min, and the slurry concentration is 30%;
[0271] The SiO2 content in the deslimed concentrate is 96.54%, and the Al2O3 content is 1.48%.
[0272] (5) Magnetic separation
[0273] Feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate;
[0274] The magnetic concentrate is fed to the next operation;
[0275] The magnetic field strength of the magnetic separator is 1.4 T, the magnetic rod medium is 1.5 mm, the magnetic separation concentration is 25%, and the pulsation frequency is 50 times / min; the SiO2 grade in the magnetic separation concentrate is 98.60%.
[0276] (6) First flotation
[0277] feeding the magnetic separation concentrate into the first flotation to obtain the first flotation tailings and the first flotation concentrate;
[0278] The first flotation concentrate is fed to the next operation;
[0279] Among them, the mass fraction of the feed concentration is 35%, SLH and ZP-01 are used as combined collectors, the mass ratio of SLH and ZP-01 is 1:2, the addition amount of the combined collector is 550g / t, the amount of water glass is 450g / t, and the SiO2 grade in the first flotation concentrate is 98.93%.
[0280] (7) Second flotation
[0281] feeding the first flotation concentrate or the gravity separation concentrate into a second flotation to obtain a second flotation tailing and a second flotation concentrate;
[0282] The second flotation concentrate is fed to the next operation;
[0283] Among them, the mass fraction of the feed concentration is 35%; the addition amount of LGB-01 collector is 120g / t; the amount of sulfuric acid is 4700g / t, the amount of HF in the second flotation is 180g / t, and the SiO2 grade in the second flotation concentrate is 99.16%.
[0284] (8) Acid leaching
[0285] subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate;
[0286] The leached concentrate is the final product;
[0287] Among them, the solid-liquid mass ratio of the second flotation concentrate and the leaching solution is 1:3; the mass fraction of the feed concentration is 30%; the volume ratio of water, hydrochloric acid and hydrofluoric acid in the acid leaching solution is 5:3:2; the acid leaching temperature is 90°C; the acid leaching time is 6h; the SiO2 grade in the leaching concentrate is 99.9237%, and the total content of impurity elements is 763ppm.
[0288] Comparative Example 1
[0289] The main difference between this comparative example and Example 1 is that the rod mill in step (3) of Example 1 is replaced by a ball mill, and the remaining operations and step parameters are the same as those of Example 1, specifically:
[0290] (3) Ball milling and classification closed circuit
[0291] Feeding the first undersize product to a second fine screen to obtain a second oversize product and a second undersize product;
[0292] The product on the second sieve is fed into a ball mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit;
[0293] Among them, the mass fraction of the feed concentration is 70%, and the ball milling is 0.5min;
[0294] All the undersize products (particle size -0.3 mm) obtained by the second fine screen are fed to the next process.
[0295] Comparative Example 2
[0296] The main difference between this comparative example and Example 1 is that step (2) in Example 1 is not included, the first crushed product obtained in step (1) is directly fed into the rod mill grinding and classification closed-loop circulation, and the remaining operations and step parameters are the same as those in Example 1.
[0297] Comparative Example 3
[0298] The main difference between this comparative example and Example 1 is that only hydrofluoric acid is used in the acid leaching process of step (8), and the remaining operations and step parameters are the same as those of Example 1.
[0299] Comparative Example 4
[0300] The main difference between this comparative example and Example 1 is that in step (2), the first crushed product is directly fed into the double-roll crusher without forming a closed-loop circulation. Specifically:
[0301] (2) Roller crushing and screening
[0302] The first crushed product is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into a first fine screen; all the undersize products obtained by the first fine screen are fed into the next operation.
[0303] Comparative Example 5
[0304] The main difference between this comparative example and Example 1 is that in step (3), all the undersize products obtained by passing through the first fine screen are directly fed into the rod mill without forming a closed-loop circulation. Specifically,
[0305] (3) Rod mill grinding
[0306] Feed all the undersize products obtained through the first fine screen into a rod mill to obtain a grinding product, and feed the grinding product into a second fine screen;
[0307] Among them, the mass fraction of the feed concentration is 70%, and the rod mill is used for 0.5min;
[0308] All the undersize products (particle size of 0.074-0.5 mm) obtained by the second fine screen are fed to the next process.
[0309] Performance data
[0310] The mineral particle size, yield and SiO2 grade obtained in each process of Examples 1-4 are shown in Table 1:
[0311] Table 1
[0312] The mineral particle size, yield and SiO2 grade obtained in each process of Comparative Examples 1-5 are shown in Table 2:
[0313] Table 2
[0314]
[0315]
[0316] In Tables 1 and 2, -2mm represents 0-2mm, -0.8mm represents 0-0.8mm, and -0.3mm represents 0-0.3mm.
[0317] According to Table 1 and Table 2, compared with Example 1, since Comparative Example 1 replaces the rod mill in step (3) of Example 1 with a ball mill, the obtained mineral is over-crushed, so that the yield of the mineral with a particle size in the range of 40-140 mesh obtained in Comparative Example 1 after ball milling is low. Although higher grade SiO2 can be obtained, the yield is low and the loss is serious.
[0318] According to Table 1 and Table 2, compared with Example 1, since Comparative Example 2 does not include step (2) in Example 1, the first crushed product obtained in step (1) is directly fed into the rod mill grinding and classification closed-loop circulation, and the crushed product is directly ground, the obtained mineral particle size is coarser, and the yield of the undersize product obtained by the second fine screen is lower, which also affects the final purification effect.
[0319] According to Table 1 and Table 2, compared with Example 1, Comparative Example 3 uses only hydrofluoric acid, while Example 1 uses mixed acid, and the purification effect is not much different. However, Comparative Example 1 uses only hydrofluoric acid, and the silicon loss is large, so the yield decreases significantly.
[0320] According to Table 1 and Table 2, compared with Example 1, in Comparative Example 4, since in step (2) of Comparative Example 4 the first crushed product is directly fed into the double-roll crusher without being preliminarily screened through the first fine screen, fine particles are over-crushed and no closed-loop circulation is formed, resulting in a lower yield of the mineral with a particle size in the range of 40-140 mesh obtained in step (3), and also affecting the final purification effect.
[0321] According to Table 1 and Table 2, compared with Example 1, in Comparative Example 5, since in step (3) of Comparative Example 5, all the undersize products obtained through the first fine screen are directly fed into the rod mill without preliminary screening through the second fine screen, fine particles are over-crushed and no closed-loop circulation is formed, resulting in a lower yield of minerals with a particle size in the range of 40-140 meshes, and also affecting the final purification effect.
[0322] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-quality quartz ore purification process, characterized in that: It includes crushing, roller crushing and screening closed circuit, rod grinding and grading closed circuit, desludging, magnetic separation, multi-stage mineral separation and acid leaching.
2. The low-quality quartz ore purification process according to claim 1, characterized in that: The crushing comprises: feeding the ore block into a jaw crusher to obtain a first crushed product; Preferably, the particle size of the first crushed product is 0-5 mm; Preferably, the ore block is quartz ore with a particle size of 0-150 mm; Preferably, the quartz ore comprises, by mass percentage: 90.0-96.0% SiO2 and impurity elements; Preferably, the impurity elements include: 0-3.0% Al2O3, 0-5.0% TFe, 0.3-3.0% K2O, 0.05-2.0% BaO, 0.03-2.0% TiO2; Preferably, the impurity minerals in the quartz ore include muscovite, limonite, hematite, barite, biotite, potassium feldspar, albite, rutile and apatite.
3. The low-quality quartz ore purification process according to claim 2, characterized in that: The roller crushing and screening closed-loop cycle comprises: feeding the first crushed product into a first fine screen to obtain a first oversize product and a first undersize product; The product on the first screen is fed into a double-roll crusher to obtain a second crushed product, and the second crushed product is fed into the first fine screen to form a closed-loop circulation; All the undersize products obtained through the first fine screen are fed to the next process; Preferably, the mesh diameter of the first fine sieve is 1.8-2.2 mm.
4. The low-quality quartz ore purification process according to claim 3, characterized in that: The rod mill ore grinding classification closed-loop cycle comprises: feeding all undersize products obtained through a first fine screen into a second fine screen to obtain a second oversize product and a second undersize product; The product on the second sieve is fed into a rod mill to obtain a grinding product, and the grinding product is fed into a second fine sieve to form a closed circuit; All the undersize products obtained by the second fine screen are fed to the next process; Preferably, the mesh diameter of the second fine sieve is 0.6-0.8 mm; Preferably, the grinding is stopped when the particle size of the grinding product is in the range of 0.1 mm to 0.8 mm; Preferably, the mass fraction of the feed concentration in the rod mill is 62% to 70%.
5. The low-quality quartz ore purification process according to claim 4, characterized in that: The desliming comprises: feeding all the undersize products obtained through the second fine screen into a stirring barrel to obtain deslimed tailings and deslimed concentrate; The deslimed concentrate is fed to the next operation; Preferably, the stirring speed of the stirring barrel is 600-1000 r / min, and the mass fraction of the slurry concentration is 20-40%; Preferably, the SiO2 grade in the deslimed concentrate is greater than 96.5%.
6. The low-quality quartz ore purification process according to claim 5, characterized in that: The magnetic separation comprises: feeding the deslimed concentrate into a magnetic separator to obtain magnetically separated tailings and magnetically separated concentrate; The magnetic concentrate is fed to the next operation; The magnetic field strength of the magnetic separator is 1.0T to 1.6T, the magnetic bar medium is 1.0 to 2.0mm, the magnetic separation concentration is 25% to 35%, and the pulsation frequency is 25 to 100 times / min; Preferably, the SiO2 grade in the magnetic separation concentrate is greater than 98%.
7. The low-quality quartz ore purification process according to claim 6, characterized in that: The multi-stage mineral separation includes gravity separation and second flotation. Or, first flotation and second flotation.
8. The low-quality quartz ore purification process according to claim 7, characterized in that: The first flotation comprises: feeding the magnetic separation concentrate into the first flotation to obtain the first flotation tailings and the first flotation concentrate; The first flotation concentrate is fed to the next operation; Preferably, the mass fraction of the feed concentration in the first flotation is 20%-40%; Preferably, the collector in the first flotation is a combined collector including SLH and ZP-01; Preferably, the mass ratio of SLH to ZP-01 is 1:(1-3), and the addition amount of the combined collector is 500-700 g / t; Preferably, the amount of water glass in the first flotation is 450-600 g / t; Preferably, the SiO2 grade in the first flotation concentrate is greater than 98.90%; Gravity separation includes: feeding the magnetic separation concentrate into gravity separation to obtain gravity separation tailings and gravity separation concentrate; feeding the gravity separation concentrate into the next operation; Preferably, the mass fraction of the feed concentration in the reselection is 10%-25%; Preferably, the amount of flushing water in the reselection is 1.0 to 2.0 t / h; Preferably, the gravity separation equipment is a spiral chute or a shaking table; Preferably, the SiO2 grade in the gravity separation concentrate is greater than 98.80%.
9. The low-quality quartz ore purification process according to claim 8, characterized in that: The second flotation comprises: feeding the first flotation concentrate or the gravity separation concentrate into the second flotation to obtain the second flotation tailings and the second flotation concentrate; The second flotation concentrate is fed to the next operation; Preferably, the mass fraction of the feed concentration in the second flotation is 30%-40%. Preferably, the collector in the second flotation is LGB-01, and its addition amount is 50-150 g / t; Preferably, the amount of sulfuric acid used in the second flotation is 3200-50000 g / t; Preferably, the amount of HF used in the second flotation is 100-300 g / t; Preferably, the SiO2 grade in the second flotation concentrate is greater than 99.15%.
10. The low-quality quartz ore purification process according to claim 9, characterized in that: The acid leaching comprises: subjecting the second flotation concentrate to acid leaching to obtain a leachate and a leaching concentrate; The leached concentrate is the final product; Preferably, the mass fraction of the feed concentration in the acid leaching is 25%-50%; Preferably, the acid leaching solution comprises water, hydrochloric acid and hydrofluoric acid in a volume ratio of 5:(2-4):(1.5-2.5); Preferably, the acid leaching temperature is 70°C to 95°C; Preferably, the acid leaching time is 5 to 7 hours; Preferably, the SiO2 grade in the leached concentrate is greater than 99.90%.